Pengaruh Model Pembelajaran Generatif Berbantuan Media Laboratorium Virtual Terhadap Kreativitas Fisika Siswa - I Nyoman Sugiana; Ahmad Harjono; Hairunnisyah Sahidu; Gunawan Gunawan (Indonesian, 2021)
Conventional teacher-centered instruction has limited the optimal development of students' creativity in physics learning. This study aimed to analyze the effect of the Generative Learning Model assisted by a Virtual Laboratory on students' creativity in physics. This research employed a quasi-experimental design using a Nonequivalent Control Group Design. The sample consisted of one experimental class, which was taught using the Generative Learning Model assisted by a Virtual Laboratory, and one control class, which received conventional instruction. Creativity data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, and the pooled-variance t-test. The results revealed a significant difference in students' creativity between the experimental and control groups. Students in the experimental class demonstrated a greater improvement in creativity than those in the control class. These findings indicate that implementing the Generative Learning Model assisted by a Virtual Laboratory promotes a more active and interactive learning environment while providing students with opportunities to explore and develop their ideas, thereby enhancing their creativity more effectively. Therefore, the Generative Learning Model assisted by a Virtual Laboratory can serve as an effective alternative instructional approach for improving students' creativity in physics learning.